2013
DOI: 10.1021/jz401014b
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Core–Satellites Nanostructures with High Chirality and Bioproperty

Abstract: In this Letter, gold nanorods (Au NRs) and gold nanoparticles (Au NPs) were assembled into core-satellites (Au NR-NPs) nanostructures using DNA as the linkers. Circular dichroism (CD) measurements of the nanoassemblies displayed two plasmonic CD (PCD) peaks in the vicinity of the surface plasmon resonance (SPR). Interestingly, the number of Au NPs in the assemblies had a significant influence on the shape and intensity of the CD line. The assemblies were enzymatically disassembled by deoxyribonuclease I (DNase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 54 publications
(67 reference statements)
0
39
0
Order By: Relevance
“…Electromagnetic hotspots formed by controlled aggregation or assembly of plasmonic nanostructures are known to be highly SERS-active. 22,46 In fact, it has been demonstrated that the contribution of a relatively small number of electromagnetic hotspots (63 out of 10 6 active sites) can be quite significant (∼25%) in the overall SERS signal, which underscores the importance of electromagnetic hotspots in the design of SERS probes. 47 Higher-magnification TEM images reveal sub-3 nm interstices that formed between the satellites on AuNS surface ( Figure 3A).…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…Electromagnetic hotspots formed by controlled aggregation or assembly of plasmonic nanostructures are known to be highly SERS-active. 22,46 In fact, it has been demonstrated that the contribution of a relatively small number of electromagnetic hotspots (63 out of 10 6 active sites) can be quite significant (∼25%) in the overall SERS signal, which underscores the importance of electromagnetic hotspots in the design of SERS probes. 47 Higher-magnification TEM images reveal sub-3 nm interstices that formed between the satellites on AuNS surface ( Figure 3A).…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…In our previous work, we found that, due to the dipole–dipole interaction between particles during the assembly of self‐assembled nanosuperstructures, a strong chiral signal is produced at the position of the surface plasmon resonance peak . Already described chiral superstructures include nanotweezers and nanotubes .…”
Section: Introductionmentioning
confidence: 99%
“…Strong chiroptical activity, together with unprecedented regulated intensities and peak positions, is not only vital for chiral plasmonic assemblies, but is urgently required for ultrasensitive and multivariable biosensing applications . Conventionally, adjusting the intensity is generally achieved by extensive synthesizing of building blocks of different sizes and myriad shapes and assembling these into a variety of predesigned chiral nanoscale assemblies, but the feasible fabrication of assemblies with tunable and strong chiroptical activity still poses great challenges …”
Section: Introductionmentioning
confidence: 99%